Clinical, biochemical and echocardiographic characteristics in children with multisystem inflammatory syndrome associated with coronavirus disease: a tertiary care experience - Fernandes D’Sa, Lorraine A. C.; Joshi, Vaishali (International Journal of Contemporary Pediatrics, 2022)
Background: We describe the clinical, biochemical and echocardiographic characteristics in children diagnosed with multisystem inflammatory syndrome (MISC) temporally associated with severe acute respiratory syndrome coronavirus 2 (SARS-Co-V-2), admitted to a tertiary care hospital in Goa, India. Methods: This was a retrospective observational study conducted at Goa Medical College, Goa, India. Parameters including demographics, clinical features, laboratory markers, medications and outcomes were obtained from patient hospital records; analyzed for patients treated for MISC (as per WHO case definition) for a period of 11 months from 01 July 2020 to 31 July 2021. Results: 30 patients (18 males) with median age of 7 years (IQR: 2 months – 12 years) were included. The proportion of children with gastrointestinal symptoms was 20 (64.5%), shock was a presenting feature in 15 (48%) and coronary ectasia and/or low ejection fraction was seen in 12 children (38.7%). Conclusions: A high index of suspicion for the diagnosis of MIS-C in children presenting with fever and Kawasaki disease like symptoms or signs of shock is recommended; since early aggressive therapy with Intravenous Immunoglobulins and methylprednisolone can have favourable outcomes.